(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and histopathological characteristics and to examine selected associations among patients with cutaneous melanoma treated at the National Hospital of Dermatology and Venereology during the period 2020-2026. Methods: A retrospective descriptive cross-sectional study was carried out on 71 patients with histopathologically confirmed cutaneous melanoma. Demographic data, presenting features, lesion characteristics, pathology findings, immunohistochemical markers, and stage at diagnosis were retrieved from medical records. Relationships between categorical variables were analyzed using Fisher’s exact test where suitable. Results: The mean age was 60.1 ± 15.3 years; patients aged 60-79 years accounted for the largest share (52.1%). Females comprised 56.3% of the study population. Among cases with available information on disease duration, the 1-5-year group was the most common (28.2%). Enlargement of a pigmented macule was the most frequent initial presentation (57.7%). Lesions were predominantly located on the foot and nail unit (90.1%). Clinical ulceration was observed in 70.4% of cases. Acral melanoma was the predominant histopathological subtype (94.4%). Breslow thickness was available for 62 cases, with the 1.01-2.0 mm category being the most common (32.3%). Histopathologically confirmed nodal metastasis at the time of diagnosis was identified in 11.3% of cases. Among the 66 patients with staging data, stage II was the most frequent stage (45.4%). Patients with Breslow thickness > 2.0 mm had markedly higher rates of both clinical and histopathological ulceration than those with Breslow thickness ≤ 2.0 mm. HMB45 was the most frequently positive immunohistochemical marker, with a positivity rate of 54.9%. Conclusion: In this study population, cutaneous melanoma occurred predominantly in older adults and showed a marked predilection for acral sites, particularly the sole, heel, and toes. Greater Breslow thickness was associated with both clinical and histopathological ulceration at the time of diagnosis.